Home security alarm system / Muhammad Bazli Zulkefli, Ahmad Saufi Lokman Fikry and Siti Azura Ramlan - Zulkefli, Muhammad Bazli; Lokman Fikry, Ahmad Saufi; Ramlan, Siti Azura (2020)
Nowadays, house burglary has become one of the concern issues in our community. These criminal acts lead to devastating consequences for the people. Due to the current situation, this project has proposed to overcome the problem by implemented technology innovation. Many people who in the situation had face loss stuff especially when it comes to their valuable belongings. It is troubling for them to face that terrible consequence. This project has focused on developing a home security alarm system in which detection occurs when there is a burglar or theft try to break in into a house or building. This project has designed by using a Passive Infrared Sensor (PIR), Arduino, and WiFi module ESP 8266 as the main component. The sensor will detect the infrared light radiating from intruders and send the information to Arduino. Then, Arduino will process the information received. This project also constructed with alarm, LED, and WiFi module ESP 8266. The alarm and the LED will activate if there is an intruder. Next, WiFi module will send a notification to the owner of the house when there is an intruder. The project is successful developed an affordable home security alarm system with applying the Internet of Things (IoT) concepts and embed a WiFi module (ESP 8266) into Arduino. At the end of this project, the system successfully functions to act as a security alarm and shows the motion detected within five meters distance. In conclusion, this project will help people be aware of burglar activity and make them alert and care about their neighbourhood. It is crucial to keep the community secure, and this product is useful for the future.